Peningkatan Produktivitas Tanah Marjinal dengan Teknologi Pengolahan Tanah Dalam (Deep tillage) - Harsono Harsono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
The study was carried out to increase the productivity of marginal soil by deep tillage method. The study was located in Mangunan, Giriredjo, Bantul, during the period of August to December 1995. Randomized Completely Block Design was employed with three replications and treatments. The treatments are : no plowing (A), soil plowing at the depth of 10 cm (B) and soil plowing at the depth of 50 cm (C). Result of the study revealed that the highest yield of Zea mays was found on the no plowed marginal soil. Those are 29,67 kw/ha for the plowed soil at the depth of 50 cm and 7,48 kw/ha for the no plowed marginal soil, respectively. Significant different of yield/ha was suspected due to more stable water supply from root zone (as indicated by higher water retention and total porosity), the lower soil penetration and soil bulk density of the plowed soil at the depth of 50 cm than at the no plowed soil. As a result a better growth yield of the plowed marginal soil at the depth of 50 cm than at no plowed marginal soil.